The Gully of Bluemansdyke - Doyle, Arthur Conan (Saga Egmont, 2022)
First published in 1881 'The Gully of Bluemansdyke' is a collection of seven short stories from the much-loved author Sir Arthur Conan Doyle. The stories are set all over the world, from Australia to Scotland and Budapest. Full of adventure, excitement and even the paranormal, tales in this collection include 'My Friend the Murderer', 'The Silver Hatchet' and 'That Little Square Box'. -